An analysis of sociodemographic, dietary and environmental determinants of allergic rhinitis and atopic eczema symptoms among adolescents in Cape Town, South Africa : findings from the International Study of Asthma and Allergies in Childhood (ISAAC) - Dearham, Astrid Chrisilda (Department of Public Health and Family Medicine, 2014)
Most analyses of International Study of Asthma and Allergies in Childhood (ISAAC) data in developing countries have suggested an increase over time in 12-month prevalence of rhinitis and eczema symptoms amongst adolescents. The objective of this study is to measure the sociodemographic, dietary and environmental risk factors of allergic rhinitis and atopic eczema symptoms amongst adolescents of the Cape Town centre of the ISAAC Phase Three study.